Beneficial Effect of Intermedin 1-53 in Septic Shock Rats: Contributions of Rho Kinase and BKCA Pathway-Mediated Improvement in Cardiac Function. Issue 5 (November 2016) - Zhu, Yu; Wu, Huiling; Wu, Yue; Zhang, Jie; Peng, Xiaoyong; Zang, Jiatao; Xiang, Xinming; Liu, Liangming; Li, Tao
ABSTRACT: Objective: Intermedin (IMD) is a calcitonin gene-related peptide shown to have a protective effect on myocardial function in ischemia-reperfusion injury. Whether IMD has beneficial effect in severe sepsis and septic shock (and its underlying mechanisms) is not known. Methods: We induced septic shock using cecal ligation and puncture (CLP). We focused on the potential beneficial effect of IMD1-53 on cardiac papillary muscle and cardiomyocytes against septic shock and its relationship with the protection of cardiac function. Results: Early (immediately after CLP) and late (12 h after CLP) administration of IMD1-53 (0.5 μg/kg) improved animal survival significantly, increased cardiac contractility and function, and improved tissue perfusion and oxygen delivery. The effect of early administration of IMD1-53 was better than that of late administration. The Rho kinase/TnI and BKCa pathways participated in the protective effect of IMD1-53 on cardiac function in septic rats. An inhibitor of Rho kinase (Y-27632) or a BKCa opener (NS1619) abolished the protective effect of IMD1-53 on cardiac function. IMD1-53 increased expression of Rho kinase in cardiac muscle and inhibited TnI phosphorylation. IMD1-53 inhibited currents in BKCa channels and intracellular calcium concentration in cardiomyocytes. Conclusions: IMD1-53 is beneficial against severe sepsis/septic shock. IMD1-53 can improve cardiac contractility and cardiac function significantly, and then improve tissue perfusion and oxygen delivery. Rho kinase and the BKCa pathways have important roles in these effects. These findings provide a new treatment strategy for severe sepsis with cardiac dysfunction.